Green Operations Management of Interbasin Water Transfer Project: An Extended Framework of Joint Pricing and Inventory Management - Huimin Wang; Liuyu Xue; Jianhui Peng; Gaofeng Liu; Zhisong Chen (Discrete Dynamics in Nature and Society)
To achieve sustainable operations management of an interbasin water transfer (IBWT) project, we proposed and analyzed decentralized and coordination decision models of water-green-degree (WGD) efforts for the IBWT project, based on the thinking of green supply chain within an extended framework of joint pricing and inventory management. Subsequently, detailed numerical and sensitivity analyses are carried out, which is followed by theoretical and practical insights. The following can be drawn from the research: (1) the IBWT project would achieve better operational performance through making WGD efforts and implementing green supply chain management. (2) Coordination strategy outperforms the decentralized one in terms of the operational performance in the management of IBWT green supply chain. (3) A revenue and cost sharing contract based on Nash bargaining could help promote coordination of the IBWT green supply chain.